Student Motivation Against Short Distance Running Numbers Athletic Learning Android Application Based - Hasan Sapri Sidik; Ine Rahayu Purnamaningsih; Tedi Purbangkara (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine the level of motivation of class VII students at SMP Negeri 1 Karawang Timur. This research is a descriptive study. The method used in this research is survey method. The population in this study were students of class VII SMP Negeri 1 Karawang Timur. The size of the subjects used in this study were 345 students of class VII. Data collection techniques with a questionnaire (questionnaire). The results showed that the motivation level of class VII students of SMP Negeri 1 Karawang Timur towards the Android Application-Based Short Distance Running Numbers Athletics was in the VERY GOOD category with a percentage of 186.76%. Intrinsic motivation with sub-indicators which include Confidence, Desire, and Self-Confidence has a value of 6839.2 or as a percentage of 136.78% in the VERY GOOD category. For extrinsic motivation with sub-indicators which include Environment, Association, and Application Media, a score of 3303.2 or 136.78% is in the ENOUGH category